2020
DOI: 10.1111/cch.12735
|View full text |Cite
|
Sign up to set email alerts
|

Parents' perspectives on participation of young children with attention deficit hyperactivity disorder, developmental coordination disorder, and/ or autism spectrum disorder: A systematic scoping review

Abstract: Background: During the early years of a child's life, participation is essential for learning and development. Children with disabilities are at risk for decreased participation. The interplay between environment and participation is identified as one of the most important factors influencing successful participation. The objective of this scoping review was to synthesize peer-reviewed literature about barriers and facilitators of participation according to the perspective of parents of children younger than 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
(79 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, their restrictive and repetitive behaviors may set them apart from other children and further limit their participation in everyday activities [ 19 ]. In addition, parents of children with ASD indicate that their child’s participation may also be impacted because parents may avoid participation outside their home due to fears of the negative perceptions of others [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, their restrictive and repetitive behaviors may set them apart from other children and further limit their participation in everyday activities [ 19 ]. In addition, parents of children with ASD indicate that their child’s participation may also be impacted because parents may avoid participation outside their home due to fears of the negative perceptions of others [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies on participation of children with disabilities have focused on school-aged children and adolescents and those with physical disabilities, while there is a lack of research on participation for young children with ASD [ 24 ]. A systematic review by Adair et al [ 6 ] found that of the 394 articles on participation that they reviewed, 105 articles focused solely on cerebral palsy, while only 37 articles focused on ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the socioenvironmental aspects that interfere with the follow-up of stimulation of children with CZS, it was found that the caregivers feel insecure to continue with the stimulation due to low education and little clarification about the CZS. Research corroborates this aspect by showing that the engagement of children with physical disabilities in stimulation services is more influenced by environmental factors (such as social support, financial resources and level of family knowledge) than by the type of disability (14) .…”
Section: Discussionmentioning
confidence: 81%
“…Despite these efforts, a study points out that it is common for caregivers of children with disabilities not to cooperate with the continuation of development stimulation, because they do not recognize themselves as competent subjects for this purpose (14) . There may also be a failure in communication or reception between rehabilitation services and the family: for example, if caregivers feel judged or if their children are ignored during the visits (15) .…”
Section: Introductionmentioning
confidence: 99%
“…This is intended, on the one hand, to sensitize psycho-social professionals to DCD characteristics and on the other hand to make children and families feel understood and supported. Recently, some researchers conducted a systematic scoping review which gave birth to guidelines focusing on family-centered care, communication with, and providing information to parents with young children with developmental disabilities considering ADHD, DCD and ASD [ 90 ].…”
Section: Discussionmentioning
confidence: 99%